FACTORS AFFECTING THE DIGITALIZATION OF THE ECONOMY AND THE FORMATION OF INDUSTRY 4.0 - Regent, Tatyana; Epikhina, Galina; Kuvshinova, Julia; Maslennikova, Anna; Sokolova, Ekaterina (Revista Inclusiones, 2020)
The article is devoted to the analysis of the digital economy development problems in the socioeconomic environment. It has been found that the digital economy is a new type of economic relations that is already present in all sectors of the world market and is rapidly developing. It has also been revealed that the digital economy could soon become the leading segment, a driver of growth and development of the socio-economic system as a whole. This is because the digital economy has some advantages over material commodity-money exchange, such as fast delivery of goods or almost instant provision of services. Another advantage of the digital economy is the lower cost of producing and executing transactions. It is proved that one of the key advantages of the digital economy in comparison with the traditional one is that electronic goods exist in a virtual form and are almost limitless